Exact density matrix elements for a driven dissipative system described by a quadratic Hamiltonian - Sh. Saedi (Nature Portfolio, 2021)
Abstract For a prototype quadratic Hamiltonian describing a driven, dissipative system, exact matrix elements of the reduced density matrix are obtained from a generating function in terms of the normal characteristic functions. The approach is based on the Heisenberg equations of motion and operator calculus. The special and limiting cases are discussed.